Future of agricultural research - Zilberman, David (International Food Policy Research Institute, 2021)
This chapter addresses some of the basic questions regarding agricultural research systems, especially in the context of developing countries, raised in the preceding chapters. Increased urbanization and urban food demand, as well as increasing per capita income, will lead to greater demand for high-value products, including fruits, vegetables, and animal-sourced foods (Chapters 9 and 10). Modern food value chains have emerged in response to such structural changes in food demand (Chapters 11 and 12). However, undernutrition, food insecurity, and poverty are persistent issues in many developing countries (Chapter 10). Building new equitable and viable agrifood systems will be one of the major issues of agricultural development in the coming decades. This chapter asks what agricultural research should be done, who should do it, and who should pay for it. A major challenging global issue in agricultural development is how to cope with climate change (Chapter 19), which accompanies deteriorating stock of natural resources (Chapter 18) and growing water scarcity (Chapter 20). Here too, the questions arise as to who should do what kind of agricultural research and who should shoulder the cost.